Systematic literature review about gamification in MOOCs. (2nd January 2023) - Jarnac de Freitas, Marta; Mira da Silva, Miguel
ABSTRACT: One of the main problems of Massive Open Online Courses (MOOCs) is the low retention rate of students and a high no-show rate. Meanwhile gamification has been gaining notoriety in the last decade within the education field. This systematic literature review explores the impact gamification has had in MOOCs, how their success is being measured, what are the theories normally associated with these gamified learning environments, and what game design elements are used as well as their implementation and outcome. We've reviewed 22 papers dating from 2014 to July 2019. Our findings are positive in terms of the outcomes, with a general increase in participation and retention on gamified MOOCs.